2001
DOI: 10.1128/jvi.75.1.420-428.2001
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant Newcastle Disease Virus with Low-Level V Protein Expression Is Immunogenic and Lacks Pathogenicity for Chicken Embryos

Abstract: Newcastle disease virus (NDV) edits its P-gene mRNA by inserting a nontemplated G residue(s) at a conserved editing site (3-UUUUUCCC-template strand). In the wild-type virus, three amino-coterminal P-gene-derived proteins, P, V, and W, are produced at frequencies of approximately 68, 29, and 2%, respectively. By applying the reverse genetics technique, editing-defective mutants were generated in cell culture. Compared to the wild-type virus, mutants lacking either six nucleotides of the conserved editing site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
1
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(133 citation statements)
references
References 37 publications
(35 reference statements)
7
121
1
4
Order By: Relevance
“…This suggests that the F protein cleavage site is not the sole determinant of NDV virulence but that other mutations in the NDV genome may cause the increase in pathogenicity. Recently, we have shown that the NDV V protein, which is produced as a result of editing of the P gene mRNA, plays a role in pathogenicity (Mebatsion et al, 2001). It was demonstrated that the level of V protein expression correlates directly with NDV virulence for chicken embryos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the F protein cleavage site is not the sole determinant of NDV virulence but that other mutations in the NDV genome may cause the increase in pathogenicity. Recently, we have shown that the NDV V protein, which is produced as a result of editing of the P gene mRNA, plays a role in pathogenicity (Mebatsion et al, 2001). It was demonstrated that the level of V protein expression correlates directly with NDV virulence for chicken embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Introductions of F and HN sequence alterations were done using the USE Mutagenesis kit (Amersham Pharmacia). Mutagenesis of the F cleavage site to generate rNDVF1 was done as described previously (Mebatsion et al, 2001). To alter the position of the HN stop codon, PCR was performed on pfl-NDV-1 using the forward primer P3F and the reverse primer P3R (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Reverse genetics can also be used to produce ND vaccines with reduced pathogenicity for chicken embryos. One such virus expresses low levels of the V protein, exhibits impaired replication, but still induces protective antibody levels in hatched chickens (Mebatsion et al, 2001).…”
Section: Vaccination Against Ndvmentioning
confidence: 99%
“…The matrix protein (M) is involved in the budding process of the newly formed virus particles (Peeples et al , 1992), while the haemagglutinin-neuraminidase (HN) and fusion protein (F), two glycoproteins anchored in the virion envelope, are involved in the binding and/or fusion to the host cell membrane, and, for HN, in the release of the newly formed virus particles (Yusoff & Tan, 2001). The P gene also encodes two non-structural proteins, called V and W, which seem to be involved in the pathogenesis of the virus (Steward et al , 1995;Mebatsion et al , 2001;Park et al , 2003).…”
Section: Introductionmentioning
confidence: 99%